Implementation of the 2013 Curriculum during the COVID-19 Pandemic at MAN Insan Cendekia Paser - Salmitha, Lely (Borneo International Journal of Islamic Studies, 2022)
The Ministry of Education and Culture has issued an emergency curriculum to deal with pandemic conditions, which has become a reference for MAN Insan Cendekia Paser in distance learning. The government provides three curriculum options that can be chosen by educational institutions, namely, continue to apply the national curriculum, implement the emergency curriculum, and simplify the curriculum independently. This attracted researchers to research the implementation of the 2013 Curriculum during the COVID-19 Pandemic Period at MAN Insan Cendekia Paser. This study uses a qualitative research approach with the subjects studied, namely teacher representatives, waka curriculum, and school principals, which were carried out with data collection techniques in the form of observations, interviews, and documentation. The validity of the researcher's data used the triangulation method. The data in this study were analyzed by data condensation steps, data presentation, and conclusion. The results of this study are that all teachers have prepared curriculum plans by compiling annual programs and semester programs based on the COVID-19 emergency curriculum. In preparing the lesson plan, all MAN IC Paser teachers have also adjusted their preparation according to the guidelines for the COVID-19 emergency curriculum. Moreover, online learning was implemented for the Presentation and learning at MAN IC Paser at the beginning of the COVID-19 pandemic. In August 2021, the implementation of learning was carried out in a limited face-to-face manner. It was carried out face-to-face in October while implementing the COVID emergency curriculum. The challenges and barriers in implementing the 2013 curriculum during a COVID-19 pandemic include less than optimal learning using practicum methods, student saturation, and difficulty in assessing student attitudes.